THE ROLE OF METACOGNITION IN READING COMPREHENSION - Mita Nur Aflah (IKIP PGRI Pontianak, 2017)
The purpose of this paper is neither to conduct such a study nor to assess students’ metacognitive awareness in reading comprehension. In particular, this paper tends to explore the theory on metacognition and the important of metacognitive strategy in enhancing ELF students’ reading comprehension. It includes a short discussion of some of the basic concepts of metacognition and review of various studies on the development of metacognition in reading comprehension. Moreover, hopefully the paper could provide teacher, educators and instructors some suggestions and to lead further studies for helping the students to increase their metacognitive awareness of reading strategies. To this end, this paper can also serve as a research reference in the field of students’ metacognitive knowledge of reading skill, particularly in reading comprehension strategies.Keywords: metacognitive reading strategy, reading comprehension.